CONFLICT OF INTERESTS AND SOCIAL SТАBILITY IN THE FIELD OF LABOUR RELATIONS - Jovanović, Predrag (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Abstract: Labour relations are characterised by strong (existential) conflict of interest between the employee and the employer. Therefore, labour relations must represent a legal term of the balance of interest of its entities, in order to be stable and have perspective. In other words, there is reciprocity of rights and obligations of the entities in labour relations. However, the employer is a stronger party, both legally and factually. The traditional task of labour law is to mitigate that legal and factual inequality of the employee and the employer to the extent necessary to ensure social security of employees and the employer himself, and social milieu and stability of the society as a whole. To this effect, appropriate limitations of the employer’s authority are incorporated into the labour relations and appropriate principles for the operation of the system of labour relations are determined.